Publicly funded Steiner education in England–Beautiful anomaly? Missed opportunity? Or both? - Mepham, Trevor Michael (Frontiers in Education, 2024)
The 1870 Education Act signalled a clear intent to provide school education on a national scale for all children in England and Wales 1 . The provision of public funds aside, over the last 150 years, there has been an intermittent debate concerning the perceived benefits and drawbacks of the control and regulation of education by the state. In broad terms, the debate has occupied a space between the libertarian views of English philosopher and political economist, John Stuart Mill (1806-1873), and those advocated by the Welsh textile manufacturer, philanthropist and social reformer, Robert Owen (1771-1858).For Owen, the provision of publicly funded education and learning opportunities to the children of the poor, uneducated masses that laboured to fuel the economic and industrial transformation of the 19 th century, was the greatest imaginable public good, and the most powerful tool for human development and social renewal. On 1 st January 1816, he gave a speech in New Lanarkshire, in which he outlined his social vision for the year 2000:"What ideas individuals may attach to the term 'Millennium', I know not: but I know that society may be formed so as to exist without crime, without poverty, with health greatly improved, with little, if any, misery and with intelligence and happiness increased a hundred-fold; and no obstacle whatsoever intervenes at this moment, except ignorance, to prevent such a state of society from becoming universal." 2 John Stuart Mill, on the other hand, while supporting the general notion that universal education and learning are unquestionably positive developments, was much more cautious about the reach and the role of the state in such affairs. In an essay -On Liberty -written in 1859, Mill (1859) wrote:"If the government would make up its mind to require for every child a good education, it might save itself the trouble of providing one.